Deviance in a social context - Cioban, Victor; Cioban-Kudelca, Smaranda (Przegląd Krytyczny, 2024)
This study consists of a critical presentation of deviance, focusing on an interdisciplinary investigation. While using a thematic literature review, we discuss the internal mechanisms of social cohesion and observe that every scholarly domain develops its own research pattern. Deviance is a highly debated phenomenon strictly relevant to social functioning. On the one hand, economists discuss it concerning social market regulation, stating that people’s actions can be explained through Weber’s rational choice theory, where social order is depicted as social capital. On the other hand, the cultural approach is profoundly influenced by a metaphysical worldview, considering the religious, historical, and aesthetical experiences. Their focus is upon the notion of morality, which is, unfortunately, not clearly defined, and its impact on the features of canon, particularly the relationship established between social taste and social distinction, which are frequently criticized by sociologists, whose opinions gravitate towards the norms, anomie, and social bond processes. After a short portrayal of the conceptual limits of social deviance, which are reflected in the Marxist, feminist, and ecological perspectives, the paper ends with our opinion on this complex issue.